1, 2, 4, 5-Tetra(diphenylphosphihyl)benzene as Novel Effective Extractant for Actinides and Lanthanides. Issue 2 (23rd February 2020) - Turanov, А. N.; Karandashev, V. K.; Аrtyushin, О. I.; Brel, V. K.
ABSTRACT: A novel polyfunctional neutral organophosphorus ligand 1, 2, 4, 5-tetra(diphenylphosphihyl)-benzene I containing four Ph2 P(O)- groups fixed on the benzene platform was synthesized and studied as an extractant for U(VI), Th(IV) and lanthanides(III) ions from HNO3 solutions. The influence of aqueous and organic phases on the extraction efficiency was elucidated. Stoichiometry of the extracted complexes was determined, and the equilibrium constants were calculated. The extraction efficiency of compound I towards U(VI)), Th(IV) and lanthanides(III) ions is significantly higher than that of its analogue V with methylene spacers between P(O) groups and a benzene ring. Compound I extracts U(VI) more effectively than tetraphenylmethylenediphosphine dioxide VIa, one of the most effective extractants of actinides and lanthanides from nitric acid solutions, but ranks below in the extraction of Th(IV) and Ln(III).